Elites, masses, and democratic decline in Indonesia. Issue 4 (18th May 2020) - Aspinall, Edward; Fossati, Diego; Muhtadi, Burhanuddin; Warburton, Eve
ABSTRACT: The current worldwide democratic regression has prompted debate about the drivers of democratic decline. One country experiencing decline is Indonesia, where most analysts blame the shift on actions of illiberal elites, casting the public as a democratic bulwark. Yet, as in other fragile democracies, regression in Indonesia has come at the hands of politicians enjoying popular support. To investigate drivers of democratic decline we ask: How democratic are Indonesian citizens when compared to the politicians they elect? We answer this question using an original, representative survey of provincial legislators, which we compare to a general survey of the Indonesian population. While both populations express overwhelming support for democratic government, we find significant differences between how elites and masses conceive of democracy, and in their commitment to liberal norms. Though neither group is a bulwark of liberal values, we find the legislators are systematically more liberal than voters. These findings challenge widely held assumptions about Indonesia's political class, and suggest a public that is either indifferent to, or supportive of, an increasingly illiberal democratic order. Our study demonstrates that comparing elite and mass attitudes to democracy and liberalism is one fruitful technique for investigating sources of democratic resilience and fragility.